Peraturan Contempt of Court Untuk Memulihkan Marwah Peradilan Akibat Pelanggaran Integritas Melalui Peradilan Ulangan - Pakpahan, Novritsar Hasintongan (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This research is based on the issue of lack of contempt of court statutes and the common practice of denigrating judiciaries in trials. Background of the study is due to common practice of integrity abuse and lack of judiciary’s dignity protection that pushes the need for contempt of court statute formulation. The paper then formulates two research questions, namely how the regulation of contempt of court would revitalize court’s dignty and how regulation can be formulated for legal remedy towards tainted legal process. The methodology of the research is based on normative research that applied statute approach, conceptual approach, case approach, and philosophical approach. The research has considered previous researches such as Probo, Perbawati, Santoso, Gayatri, and Rachman’s research. The development of contempt of court in the last 5 to 10 years showed that contempt of court regulation has been better formulated through Act 1 of 2023, but it didn’t specify types of contempt of court. The result showed that contempt of court statute should regulate specifically regarding act of denigrating court’s dignity and reformulation of retrial legal remedy for tainted legal process.